KAJIAN PROTOTIPE ROTARY DRYER BERDASARKAN KECEPATAN PUTARAN SILINDER PENGERING DAN LAJU ALIR UDARA TERHADAP EFISIENSI THERMAL PENGERINGAN BIJI JAGUNG - Effendy, Sahrul (Politeknik Negeri Sriwijaya, 2018)
Drying is one of the important processes in food handling. This is because the drying process can extend the shelf life of food products so that it can be consumed longer. The purpose of this study was to design a biomass-fueled rotary type dryer and to analyze the effect of the flow rate on the melting and thermal efficiency of the dryer to determine the optimum condition of the dryer. One of the drying equipment that can be used is a rotary type dryer. The heat source of the dryer may come from a burning heat source. The use of biomass fuel here is to reduce as well as replace the use of fossil fuels considering its existence is increasingly thinning each year. Therefore, this research will be observed from the use of coconut shell fuels on thermal efficiency of rotary type drying machine. Based on the test results of variation of hot air flow rate for drying 15 minutes it is known that the air flow rate is very influential on efficiency and decreasing of water content. Based on SNI for moisture content, the optimum condition that can be used is the air flow rate of 12 m/s with thermal efficiency of 66.55% obtained moisture content of 14.22%. Besides that, The efficiency of thermal rotary dryer increases with increasing speed of rotation. The highest efficiency value obtained at the condition of 24 RPM in 15 minutes is 74.14%